Somatomammotrophs, FSH-LH and ACTH-LH cells, the bihormonal cells in buffalo pars distalis adenohypophysis - Khan, Massarat; Saigal, Rajya Pal (The Indian Journal of Animal Sciences, 2012)
Using differential staining methods while hormone producing cells were demonstrated in the pars distalis adenohypophysisof 52 buffaloes of either sex and aged 1 week to adult, the occurrence of bihormonal cells including theSomatomammotrophs, FSHÂ· LH and ACTH-LH cells was evidenced. They were relatively more frequent in older animals.Different types of secretary granules within the same cell were either intermingled, or were intermixed in one of its partand localized singly in the other part, or they were localized separately in its different parts. Their possible significancehas been discussed.